Administrative Judicial Oversight of Decisions to Appoint Public Employees in the State of Kuwait - Al-Omar, Barak; Tannar, Hamoud (Journal of Legal Sciences, 2026)
In this topic, we discussed the administrative judiciary’s oversight of the appropriateness of public employee appointment decisions. Through this topic, we aimed to identify the effectiveness of the judicial oversight exercised by the Administrative Cassation Court on the appropriateness of public employee appointment decisions, through monitoring the terms of appointment and verifying the extent of compliance. Management controls the appointment process As well as oversight of the discretionary authority granted to the administration during the appointment process, the descriptive approach has been applied, and in this matter we have reached several results, including that judicial oversight is particularly important for verifying the legitimacy of administrative decisions related to appointment in particular and related to public employment in general, as it works To verify the extent of the administration’s commitment to the principle of legality in the appointment process. There are also powers and powers granted by the legislator to the judiciary to exercise its oversight over the decisions and actions issued by the administration, especially over the process of appointing a public employee. The judiciary’s approach to appointment was to verify the guarantees established by the legislator to protect the public employee against the administration and to guarantee his rights during this stage. In this matter, we have come up with several recommendations, including the necessity of activating the self-monitoring role of the administration so that the senior management has oversight over the lower-ranking and progressive administration, thus activating the supervisory role on the administrative decisions issued by it, especially related to the appointment of the public employee, and the importance of reducing the duration of the administrative grievance so that it is within It is possible to quickly resort to the judiciary to carry out its oversight tasks over the administration’s work related to the appointment of the public employee. The necessity of choosing appropriate appointment methods that ensure the presence of the most qualified and qualified person to assume the responsibilities of the public job, and narrowing the discretionary authority granted to the administration in the appointment process, and the importance of presenting the ministerial decisions regarding the appointment of the leadership functional group to the judiciary in order to activate the role of the judiciary in those decisions until the presence of the appropriate employee is verified. In the right place.